Rise of the modern west - Shrikant Paul (NewDelhi : Academic Aspirations, 2022)
The western world also known as the west refers to various regions, nations and states,depending on the context most often including at least parts of Europe,Australasia,and the Americas.By the 17th century there was already a tradition and awareness of Europe.a reality stronger than that of an area bounded by sea mountains,grassy plains,steppes,or deserts where Europe clearly ended and Asia began.By far the best and handiest account of the rise of modern west.Being strictly according to syllabus this book is a boon to student and a serviceable work references for the cultivated general readers.
Includes bibliographical references and index.
Keywords: History